SISTEM PEMASARAN DAN PROMOSI SENTRA PENGRAJIN BATIK DI KAMPUNG TEMATIK DURENAN INDAH KOTA SEMARANG TAHUN 2017-2025 - Fauzan Syahru Ramadhan; Alma Savana Fajriyansyah; Salimah Zahiyyah Muna; Nada Shifa (KRONIK : Journal of History Education and Historiography, 2025)
This research focuses on examining the marketing and promotion system of batik artisan centers in the Thematic Village of Durenan Indah, Semarang City. The majority of Durenan Indah batik artisans generally use a combinative marketing and promotion strategy with conventional and digital approaches. The purpose of this article is to identify and analyze the most effective challenges and promotional strategies to improve the competitiveness of Durenan Indah's batik products in local and national markets. The research method used in this article is a combination of observational and historical methods enriched with a socio-economic approach. The results show that the majority of artisans still rely on traditional word-of-mouth marketing patterns, although most have digital platforms. The main challenge is the limited technological literacy among artisans, the majority of whom are elderly, as well as the lack of significant impact of online promotions that have been conducted. Therefore, as a solution, they rely on partner sales, regular exhibitions, pamphlet distribution, and batik education that creates a personalized experience.